Superficial brachial artery - A case report with commentaries on the classification - Edward Clarke; Agata Mazurek; Maciej Radek; Andrzej Żytkowski; Wojciech Twardokęs; Michał Polguj; Grzegorz Wysiadecki (Elsevier, 2021)
Variations of the brachial plexus and median nerve relationships with the axillary and brachial artery may be significant to anatomists, radiologists, anesthesiologists, and surgeons. In some cases, the coexistence of anatomical variations of the nerves and vessels may also be a source of conflict between individual structures, e.g., entrapment neuropathy of the median nerve due to atypical (superficial to the nerve) course of the brachial artery.The presented report describes coexisting anatomical variations in the neurovascular topography within the axillary fossa, arm, forearm, and hand. The presence of the superficial brachial artery originating from the second part of the axillary artery was observed. Atypical common steam for the subscapularis, posterior humeral circumflex, double profunda brachii, and superior ulnar collateral arteries was also found deep to the median nerve roots. In the forearm, the persistent median artery contributing to the blood supply of the hand was exposed. The classification issues were also discussed.